Interpretation of Verses on Women in Islamic Law Politics - Lathifah, Amalia (MILRev: Metro Islamic Law Review, 2023)
In organizing a government in a democratic country, it must represent women's participation and embrace the aspirations of all levels of society because the aspirations of women that will be conveyed are the needs expected by different communities and must not be impartial. How can women be represented if there is still a shortage of female legislators? Therefore, patriarchal culture must be eliminated from public life, especially in politics, because basically, everyone has the opportunity and position to enter politics without male legitimacy having the right to do so. Gender equality aims to equal participation of men and women in decision-making processes and various areas of life, both in public and domestic services. Keywords: women, politics, power.